The Influence of Transformational Leadership Style , Discipline and Job Satisfaction on the Performance of Public Vocational School Teachers in Bima City​ - Muhammad Badrun; Hermanto Hermanto; Mery Noviyanti; Syati Irawati; Sri Astuti Handayani (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research examines the influence of transformational leadership, work discipline, and job satisfaction on the performance of public vocational school teachers in Bima City. Utilizing a quantitative associative research paradigm, the study sampled 108 teachers from a population of 381 using probabilistic random sampling. Data were analyzed through classical assumption testing, descriptive statistics, and multiple regression analysis using SPSS 25. Results indicate that transformational leadership significantly enhances teacher performance, characterized by leaders with clear vision, creativity encouragement, and individual support. Work discipline also positively affects performance, ensuring order and optimal task execution. Job satisfaction similarly has a significant positive impact, with higher satisfaction leading to improved performance. Combined, transformational leadership, work discipline, and job satisfaction account for a significant portion of the variance in teacher performance. The findings confirm that effective leadership, robust discipline, and job satisfaction are critical for enhancing teacher performance, emphasizing a multidimensional approach in educational management. This research contributes to the literature by integrating these three variables, highlighting their combined impact in the educational context of Bima City. Future research should explore additional factors influencing performance to further optimize educational outcomes.